Eficiencia del sistema de emisión electrónica y el cumplimiento de obligaciones tributarias en las mypes de Iquitos año 2022 - Laiche Hidalgo, Seky Luceth (2023)
The objective of this investigation was to determine the relationship between the efficiency of the electronic issuance system and compliance with tax obligations in the MYPES of Iquitos in the year 2022; I chose to be an applied type study, with a descriptive-correlational level and non-experimental design, I included 245 Mypes as a study population; For the collection of information, the survey technique and the questionnaire were used as an instrument. In the result, it was contrasted that the electronic issuance system is qualified as high (37%), this is because the system always makes the company more innovative and attractive to its customers; as well as the system will almost always avoid carrying out the processes of manual sealing and storage in file. On the other hand, compliance with tax obligations in Mypes is high (41%) because they almost always have someone designated to pay taxes in their company; as well as always have the computer system installed that allows tax control by the collecting entity. It is concluded that there is a significant relationship between the efficiency of the electronic issuance system and compliance with tax obligations in Mypes, contrasted with a coefficient of 0.688 (positive medium) and a significance of 0.000.